Crop Diversity and Economic Change - Smale, Melinda; King, Amanda (International Food Policy Research Institute, 2005)
As isolated communities have become progressively more linked into global production systems, understanding the impact of economic change on crop diversity has become increasingly important. Although there is little conclusive evidence, it has been hypothesized that processes of economic change and market integration pose some of the greatest threats to crop genetic diversity